Sistem Jaringan Internet Gateway Berbasis Dua Internet Service Provide - Agus Sugiharto (JURNAL MITRA MANAJEMEN, 2014)
AbstractIncreased the usage of the internet connections for bussiness comunication makes thecompany must provide the large bandwidth and reliable for the connection.While a connection having problem will makes crash for bussiness comunication ofcompany. The solution by adopted the internet connection from 2 different of ISP (InternetService Provider). And implementing a load balancing technique that is combine thebandwidth of the two different ISPs and fail over techniques used to switch the connectionto another ISP when there is interference on one of the existing connections. From theexperience of the company's business disruption due failure of Internet connection sinceusing a single ISP and management will implement a multi-ISP internet connection toensure business continuity when one of Internet connection is disrupted.